CONSTRAINED STABLE GENERALIZED PREDICTIVE CONTROL - Rossiter, J; Kouvaritakis, B (1993)
Quadratic programming provides an obvious means of handling constraints within the context of generalised predictive control (GPC). However the resulting algorithm may be computationally demanding, is not robust with respect to infeasibility, constraint redundancy and degeneracy, and has no attendant general stability properties. An alternative optimisation procedure is proposed and used in conjunction with stable GPC to overcome all these difficulties.